2010
DOI: 10.1002/art.27327
|View full text |Cite
|
Sign up to set email alerts
|

High versus low dosing of oral colchicine for early acute gout flare: Twenty‐four–hour outcome of the first multicenter, randomized, double‐blind, placebo‐controlled, parallel‐group, dose‐comparison colchicine study

Abstract: Objective. Despite widespread use of colchicine, the evidence basis for oral colchicine therapy and dosing in acute gout remains limited. The aim of this trial was to compare low-dose colchicine (abbreviated at 1 hour) and high-dose colchicine (prolonged over 6 hours) with placebo in gout flare, using regimens producing comparable maximum plasma concentrations in healthy volunteers.Methods. This multicenter, randomized, doubleblind, placebo-controlled, parallel-group study compared self-administered low-dose c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
275
0
31

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 448 publications
(316 citation statements)
references
References 20 publications
10
275
0
31
Order By: Relevance
“…The dependent variable was a binary indicator for receiving colchicine within 30 days after diagnosis, and independent variables were constructed based on the month of diagnosis in order to estimate the linear trend in the log odds of receiving colchicine, separately from January 2009 to September 2010 and from January 2011 to December 2012, as shown in the model, Logit{Pr(Y i =1)}=b 0 + b 1 T 1i +b 2 T 2i +b 3 Post i , where Y is the indicator of colchicine dispensing, T 1 is a time variable that represents when each patient was diagnosed with gout as the number of months after January 2009, T 2 is a time spline that begins in January 2011, and Post is a binary indicator of being diagnosed in January 2011 or after. The 90-day skip period corresponds to the transition time provided in the FDA's order enforcing Colcrys' market exclusivity.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The dependent variable was a binary indicator for receiving colchicine within 30 days after diagnosis, and independent variables were constructed based on the month of diagnosis in order to estimate the linear trend in the log odds of receiving colchicine, separately from January 2009 to September 2010 and from January 2011 to December 2012, as shown in the model, Logit{Pr(Y i =1)}=b 0 + b 1 T 1i +b 2 T 2i +b 3 Post i , where Y is the indicator of colchicine dispensing, T 1 is a time variable that represents when each patient was diagnosed with gout as the number of months after January 2009, T 2 is a time spline that begins in January 2011, and Post is a binary indicator of being diagnosed in January 2011 or after. The 90-day skip period corresponds to the transition time provided in the FDA's order enforcing Colcrys' market exclusivity.…”
Section: Methodsmentioning
confidence: 99%
“…3 The trial randomized 184 patients to receiving placebo (n=58), a low-dose colchicine regimen (n=74) that had been recommended by professional society treatment guidelines, 4 and a high-dose regimen (n=52). After 1 week, gout patients in the low-dose regimen reported good symptom management and fewer adverse events than the longer regimen.…”
Section: Introductionmentioning
confidence: 99%
“…All subjects provided written informed consent before study participation, which was conducted in accordance with the US Code of reported in the US prescribing information [4], reviews [5,9], and studies in young subjects [10,11], but the potential effect of age per se on drug disposition of this formulation has not been formally investigated until now. The objective of this study was to compare the pharmacokinetics of colchicine following the oral administration of a single 0.6 mg tablet of the approved colchicine formulation when given to young (18-30 years of age) and elderly (≥60 years of age) healthy subjects following an overnight fast.…”
Section: Methodsmentioning
confidence: 99%
“…The AGREE trial demonstrated that low-dose colchicine (1.2 mg, followed by 0.6 mg one hour later) for an acute gout flare was as effective as the higher dose regimen, with a lower incidence of gastrointestinal adverse effects. 7 Although this trial was small and conducted in patients with acute gout of less than 12 h duration, this study caused Australia to change its prescribing guidelines. 8 Already in place in Australia is the stipulation that the maximum quantity able to be dispensed is 30 tablets, with a maximum of five repeats i.e.…”
Section: Introductionmentioning
confidence: 99%